When Paolo Borsellino spoke to students about the Mafia (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
The aim of this research is to analyze the reasons of the ‘ndrangheta expansion in Germany and to point out the ways the ‘ndrangheta is able to infiltrate a non- traditional territory. In this regard, two case studies will be taken into consideration - Pollino and Stige - in order to explain the main features of this infiltration process.
Keywords: ‘ndrangheta; migration process; expansion strategies; colonization